Measurements and applications of δ2H values of wood lignin methoxy groups for paleoclimatic studies. (15th September 2021) - Greule, Markus; Wieland, Anna; Keppler, Frank
Abstract: Stable hydrogen isotope values of wood lignin methoxy groups ( δ 2 HLM ) are increasingly applied to reconstruct the stable hydrogen isotope composition of precipitation ( δ 2 Hprecip ) and mean annual temperatures (MAT) of mid latitudes regions. Recently, the analytical procedure for measuring δ 2 HLM values was considerably improved by the availability of new reference materials that are in full accordance with the requirements of normalising stable isotope measurements. Using this improved procedure we determined the δ 2 HLM values of tree rings from 40 geographical locations. Using these values, we present a revised relationship between δ 2 HLM and δ 2 Hprecip which is: δ 2 Hprecip [mUr] = ( δ 2 HLM [mUr] + 206 mUr)/0.67. In addition, a new equation for reconstructions of MAT is: MAT [°C] = ( δ 2 HLM [mUr] + 272 mUr)/3.04 [mUr/°C]. We provide a simple numerical model that explains the observed biosynthetic isotope fraction pattern between δ 2 HLM and δ 2 Hprecip . Finally, we applied the new equations to a previous data set for wood samples collected close to the Hohenpeißenberg Meteorological Observatory in Germany. The data set included a 100-year-chronology (1916–2015) from nine tree ring cores removed from four beech trees. The MAT from δ 2 HLM values reconstructed for this geographical location was 7.96 ± 2.17 °C and in very good agreement with the observed mean MAT of 7.82 ± 0.75 °C during this time period. Therefore, we conclude that the revised relationships between δ 2 HLM, δ 2 Hprecip and MAT provide the basis for reliable application for paleoclimate reconstructions. Graphical abstract: Image 1 Highlights: New measurements and evaluation of δ 2 HLM values of tree ring data. Revised relationship between δ 2 HLM values and tree source water. Biosynthetic pathway to explain the isotope fractionation between precipitation and methoxy groups. Equation for calculation of precipitation: δ 2 HPrecip [mUr] = ( δ 2 HLM [mUr] + 205 mUr)/0.67 Equation for mean annual temperature: MAT [°C] = ( δ 2 HLM [mUr] + 272 mUr)/3.04 [mUr/°C].